2005
DOI: 10.1177/14732300050330s106
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular and Vascular Remodelling – Effects of the Angiotensin II Receptor Blocker Telmisartan and/or the Angiotensin-Converting Enzyme Inhibitor Ramipril in Hypertensive Patients

Abstract: Angiotensin II induces inflammatory activation of vascular smooth muscle cells and can cause left ventricular hypertrophy (LVH). Telmisartan is an angiotensin IIreceptor blocker with demonstrated beneficial effects on cardiac and vascular structure and function in animal models. The angiotensin-converting enzyme inhibitor ramipril also reduces ventricular and vascular remodelling. The open-label study observed 75 treatment-naïve, moderately or severely hypertensive (systolic blood pressure 160 -190 mmHg, diast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
6

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 26 publications
(19 reference statements)
0
22
0
6
Order By: Relevance
“…Furthermore, the carotid IMT represents structural changes like wall thickening and the formation of atherosclerotic plaques, which are correlated with a greater incidence of atherosclerosis in the coronary circulation and other large arteries [19] . Telmisartan has been shown to cause an insignificant reduction in AI [18] and significant decreases in both BNP [20] and IMT [21] . In the present study, telmisartan-based therapy also tended to decrease the AI and to regress the IMT, consistent with the above-mentioned studies, whereas telmisartan-based therapy did not decrease the BNP.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the carotid IMT represents structural changes like wall thickening and the formation of atherosclerotic plaques, which are correlated with a greater incidence of atherosclerosis in the coronary circulation and other large arteries [19] . Telmisartan has been shown to cause an insignificant reduction in AI [18] and significant decreases in both BNP [20] and IMT [21] . In the present study, telmisartan-based therapy also tended to decrease the AI and to regress the IMT, consistent with the above-mentioned studies, whereas telmisartan-based therapy did not decrease the BNP.…”
Section: Discussionmentioning
confidence: 99%
“…One small-scale study has shown that a combination of telmisartan and ramipril produced greater regression of LVH than either monotherapy. 23 A similar observation was made in patients with type 2 diabetes and LVH on dialysis therapy when treated with the ARB losartan, the ACE inhibitor enalapril, or a combination of losartan plus captopril. 24 This hypothesis is being tested in The ONTARGET Trial Programme (Fig.…”
Section: Ontarget Trial Programmementioning
confidence: 83%
“…Conduit patency requires the following: the conduit must have antithrombotic properties [13]; intima hypertrophy must not progress in anastomoses between the MPA and the conduit [29], the intima should be covered with neo-endothelial cells [30] and the flexibility and histological form of the valve in the conduit should be maintained [27]. Although Denacol exerts an antithrombotic effect [19], intima hypertrophy in anastomoses has been demonstrated in humans due to delayed healing of the vessel after positioning a small-caliber artificial vascular graft treated with antithrombotics [22]. On the other hand, the autografts used in autologous vascular transplantation have antithrombotic effects derived from self endothelial cells, and such grafts might be highly reliable [29].…”
Section: Discussionmentioning
confidence: 99%